The Effect Of Special Exercises On The Development Of Some Physical Abilities and Fundamental Skills Of Third Year Futsal Female Students of Physical Education and Sport Sciences College / University of Baghdad - Abedulwahed, Amera; Abed, Shimaa; Laiz, Kholoud (Journal of Physical Education, 2018)
The Effect Of Special Exercises On The Development Of Some Physical Abilities and Fundamental Skills Of Third Year Futsal Female Students of Physical Education and Sport Sciences College / University of Baghdad The importance of the research lies in factors that affect the teaching process in futsal because it requires metal abilities in performing these skills. The problem of the research lies in physical abilities weakness in third year students of physical education and sport sciences/ university of Baghdad that negatively affect their level of learning futsal skills. The researchers aimed at developing some physical abilities and learning some skills in third year students’ futsal skills. They hypothesized significant statistical differences between pre and posttests in both groups in physical abilities and learning futsal skills. The researchers used the experimental method. The subjects were (30) third year female students. The program lasted (8) weeks with (16) teaching units for (90) minutes. The data was collected and treated using proper statistical operations to conclude that using the teaching program led to the development of some physical abilities and learning futsal skills. Finally they recommended using this program for developing the teaching process.